(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2024)
Introduction: The journey of medical life specially in the military environment is a very stressful for medical cadets. Objectives: To determine stress in 1st year medical cadets of Armed Forces Medical College. Methods: Out of 124 medical cadets, 117 were conducted based on a well established questionnaire that included different established factors of stress. The methodology and purpose of study was well explained to all the cadets and consent was obtained. In this study, the Medical student Stressor Questionnaire with small cadetship related factor 24(MSSQ) was used to identify sources of stress. Each of the questions in this questionnaire can be a potential source of stress in cadet in his academic life. Data were analyzed with SPSS v.12. Relation between variables was assessed with chi-square test with a significance level of 0.05% Results: Of the 124 total cadets, present 117 received questionnaires and completed them returned them. Out of 117 cadets, 82(70%) were female and 117(100%) were unmarried. Moderate stress (1.87) experienced in academic factors as well social factors. Bangla medium students facing relatively more stress than English version background students. Conclusion: This finding suggests, the very medical education is full of multi varieties stressors. More so cadetship accentuates the stress further in medical life. Now the time has come to think the policy maker involved in medical education. Their realistic thinking to reorganized the curriculum according to time limit to ensure a stress free environment as much as possible in the 1st year of MBBS. JAFMC Bangladesh. Vol 19, No 1 (June) 2023:15-17